Analisis Klasifikasi Konten Digital dan Implementasi Pemasaran Syariah dalam Memperkuat Citra Merek Islami Brand Zakiah Hijab - Angelie Kartika Mar'atus Sholikha; Ani Faujiah (Fakultas Syariah IAIN Kerinci, 2026)
This research addresses the dynamic growth of Muslimah fashion digital marketing on Instagram alongside the rising phenomenon of digital content violating Islamic law, which led to the ban of over 1.3 million negative contents by the government. This study aims to analyze content classification based on engagement metrics and evaluate Sharia marketing characteristics on the Instagram account @zakiahhijab in strengthening its Islamic brand image. Employing a descriptive qualitative method with a netnographic approach, data was collected through digital observation of likes and views to calculate the Engagement Rate (ER), combined with online in-depth interviews via WhatsApp with the owner, HRD, and digital marketing team. The netnographic results reveal a healthy overall ER of 3.15%, driven by Spiritual Education (3.23%), Modern Content (1.73%), and Pure Promotion (1.33%). Furthermore, @zakiahhijab successfully integrated the four Sharia marketing characteristics (Rabbaniyyah, Akhlaqiyyah, Al-Waqi'iyyah, and Al-Insaniyyah) through informative fiqh content, ethical lifestyle trends, agile algorithmic evaluations, and humanistic services. In conclusion, the synergy of adaptive content classification and Sharia compliance builds loyal consumer trust, effectively converting 70% of digital interactions into offline physical store transactions.